Burden of infectious diseases among undocumented migrants in France: Results of the Premiers Pas survey - Vignier, Nicolas; Moussaoui, Sohela; Marsaudon, Antoine; Wittwer, Jérome; Jusot, Florence; Dourgnon, Paul (Frontiers in Public Health, 2022)
Introduction An increase in migration rates to the European Union has been observed over the last few years. Part of this migrants are undocumented. The aim of this work was to describe the reported frequency of infectious diseases and their associated factors among unselected sample of undocumented migrants in France. Methodology The Premier Pas survey is a cross-sectional epidemiological survey of a random sample (two-stage sample design) conducted among undocumented migrants recruited in Paris and the Bordeaux region, in places and facilities likely to be frequented by undocumented migrants. The percentages were weighted. The analysis was performed using Stata 15.1 software. Results A total of 1,223 undocumented migrants were recruited from 63 places and facilities, with a participation rate of 50%. Most of them were between 30 and 40 years of age (36%), 69% were men, aged mainly 30 to 40 (36%) years old, from sub-Saharan Africa (60%) or North Africa (25%), and 60% had arrived less than three years earlier. Among the participants, 24.8% declared a poor perceived health status and 33.5% a chronic health condition. Dental infections concerned 43.2% of the participants. Apart from dental issues, 12.9% reported suffering from at least one infectious disease: HIV infection (3.5%), chronic hepatitis B virus infection (3.1%), upper respiratory tract infection (1.7%), skin mycosis (1.2%), skin and soft tissue infection (0.8%), chronic hepatitis C infection (0.8%), urinary tract infection (0.7%), lower respiratory tract infection (0.7%), scabies (0.3%), tuberculosis disease (0.2%), vaginal mycosis (0.6%), and herpes (0.1%). Regarding HIV, HBV, and HCV infections, 56%, 71% and 89% respectively were diagnosed after their arrival. Chronic viral infections were more often reported by undocumented migrants from sub-Saharan Africa and Latin America. In multivariate analysis, a higher risk of reporting chronic viral infection was observed among people food insecure. Conclusions This original study on a large random sample confirms the frequency of infectious diseases among undocumented migrants in France and the importance of integrating their screening during a health Rendezvous and their management into an early access to care and an inclusive medico-psycho-social management.